The landscape, product and resource. The experience of Contrada Bricconi in the Orobic Alps - Caterina Franco (ArchAlp, 2022)
The project of Contrada Bricconi started out as Giacomo Perletti’s dream. Born in 1986, he is a farmer and the symbol of the great passion that has driven the development project of a farm that has existed since 2010, which was when an agreement was signed between the newly founded company and the municipality of Oltressenda Alta. The agreement provided for the concession of some buildings owned by the municipality in Contrada Bricconi, an ancient stone farm settlement dating back to the 15th century and located at around 900 meters above sea level, on the border of the Parco delle Orobie Bergamasche in Val Zurio, a valley situated at the side of the Serio River basin. Since that day, the company has seen a surprising convergence of multiple people, institutions, and initiatives. Over the years, they have contributed to the realization of an ambitious project aimed at reintroducing an agricultural activity in the contrada, which had been in a state of semi-abandonment, redeveloping the existing buildings while preserving the landscape, offering the appropriate catering and hospitality for the mountain context, ensuring the economic sustainability of the new-born company. The history of Contrada Bricconi tries to teach that the landscape is itself the product of a rural society that has shaped the vegetation, topography, infrastructures, and settlements over the centuries. The return of agricultural activities in the mountains, albeit intervening on pre-existing ecological and social balances, is essential to ensure the preservation of the local heritage, which needs people’s presence and work to survive.